Community participation in the CSR existence of PT Pertamina DPPU Ngurah Rai - Suarta, Gede; Dananjaya, I Gusti Agung Nyoman; Utami, Dhita Hardiyanti (International research journal of management, IT and social sciences, 2021)
To support the government's efforts to protect and increase the Bali Starling population, PT Pertamina (Persero) DPPU Ngurah Rai through its Corporate Social Responsibility (CSR) Program has implemented the Bali Starling Conservation and Breeding. The purpose of this study is to analyze how the level of community participation and the factors that influence the level of community participation in the existence of PT Pertamina (Persero) DPPU Ngurah Rai CSR in Sibang Kaja Village, Abiansemal District, Badung Regency. This research was conducted in Sibang Kaja Village and the selection of this location was determined purposively. The population in this study amounted to 235 families while the sampling technique in this study used the simple random sampling method of 70 people. Data analysis in this research is descriptive qualitative and quantitative. The results showed that the level of community participation in the existence of PT Pertamina's CSR in Sibang Kaja Village was in the high category with a cumulative score of 4.15. While the factors that influence the level of community participation in the existence of PT Pertamina's CSR in Sibang Kaja Village include (1) Internal factors consisting of awareness, education, and income, (2) External factors consisting of village government and NGOs/Foundations.